Primagravida Application Usability And User Satisfaction As A Digital Health Initiative For Pregnancy Educational Media And Remote Rural Monitoring - Wiwin Lismidiati; Dimas Sumunar; Happy Indah Kusumawati; Mia Purnama (Journal of Community Empowerment for Health, 2023)
Introduction: Nutritional status during pregnancy is one of the critical factors in determining maternal and fetal development, affecting birth weight, perinatal mortality, and infant growth. Regular monitoring of pregnant women’s health is crucial as preventive measures and promotive approaches for both mother and fetus. Primagravida, a web-based system, was developed to assist pregnant women in rural areas in monitoring their health, especially during the COVID-19 pandemic. This study aimed to evaluate usability and user satisfaction in using Primagravida. Method: Quantitative descriptive research with a cross-sectional design was employed. The study was conducted in the Kalibawang Primary Health Center (PHC) service area between June - October 2021. Seventy-nine pregnant women participated in this study. Pregnant women were registered and observed for their pregnancy profile through a web-based service integrated with PHC maternal and child health care. In evaluating the system usability, the current study utilized System Usability Scale (SUS), while a modified users’ satisfaction questionnaire was employed to capture participants’ perceptions. Results: Results indicated that most participants were satisfied with the benefits, information relevance, content adequacy and clarity, platform availability, and up-to-the-minute curated knowledge provided by the system. Utilization of this system reduced the number of visits to PHC since health monitoring could be performed virtually. Regarding system usability, respondents reported a score of 70, and the average score of respondents was 66. Conclusion: Pregnant women have adopted the Primagravida application to monitor their health and fetal status in Kalibawang District, Kulon Progo. Feature development is required to accommodate the upcoming demands of holistic maternal and perinatal care.